Novel Small Molecule Inhibitors That Prevent the Neuroparalysis of Tetanus Neurotoxin - Giulia Zanetti (MDPI AG, 2021)
Tetanus neurotoxin (TeNT) is a protein exotoxin produced by Clostridium tetani that causes the deadly spastic neuroparalysis of tetanus. It consists of a metalloprotease light chain and of a heavy chain linked via a disulphide bond. TeNT binds to the neuromuscular junction (NMJ) and it is retro-axonally transported into vesicular compartments to the spinal cord, where it is released and taken up by inhibitory interneuron. Therein, the catalytic subunit is translocated into the cytoplasm where it cleaves its target protein VAMP-1/2 with consequent blockage of the release of inhibitory neurotransmitters. Vaccination with formaldehyde inactivated TeNT prevents the disease, but tetanus is still present in countries where vaccination coverage is partial. Here, we show that small molecule inhibitors interfering with TeNT trafficking or with the reduction of the interchain disulphide bond block the activity of the toxin in neuronal cultures and attenuate tetanus symptoms in vivo. These findings are relevant for the development of therapeutics against tetanus based on the inhibition of toxin molecules that are being retro-transported to or are already within the spinal cord and are, thus, not accessible to anti-TeNT immunoglobulins.